Preparation and Optimization of Microwave-Assisted Ball-Milled Olmesartan Medoxomil with Chitosan Using Full 3^2 Factorial Design - Gurav, Atul Shivaji; Kulkarni, Ajit Shankarrao (Indian Journal of Pharmaceutical Education and Research, 2023)
Introduction: The anti-hypertensive drug Olmesartan Medoxomil (OLM), a BCS II drug, works by inhibiting the action of angiotensin II on AT1 receptors. Objectives: The purpose of the study was to enhance solubility and stability by altering crystalline form, which reduces cost and dose burden of the pharmaceutical industry. In the current study, OLM formulation was prepared by using a full 3 level 2 factorial design with chitosan and neusiline as independent factors. Materials and Methods: Chitosan, a hydrophilic and stabilizing polymer, was used to enhance solubility and stability with the help of neusiline as a surfactant. Formulation was prepare using microwave-assisted ball milled technology. Results and Discussion: In comparison to the pure drug, phase solubility study shows the ternary mixture's saturation solubility was around 12 times higher. Physical interaction between polymer and OLM was confirmed from the FTIR study, DSC graph, SEM surface morphological study and NMR study. The drug's altered crystalline form has been confirmed by XRD, which could alter its solubility and rate of dissolution. The optimized batch obtained from factorial design was used for electrically operated ball milling. This demonstrated a notable improvement in the solubility, stability, and dissolving rate. Conclusion: As a result, using chitosan with a microwave assisted ball milling process can be a novel breakthrough in enhancing the bioavailability of any BSC II medicines.
Keywords: Microwave-assisted milling technology; Chitosan; Olmesartan; Neusiline; Factorial Design